Analisis Pengaruh Dana Pihak Ketiga, Total Aset, dan Non-Performing Finance Terhadap Pembiayaan Bagi Hasil - Syawal Harianto; Saparuddin Siregar; Sugianto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
The purpose of this study is to know and analyze the factors that affect total revenue-sharing financing in sharia business units in Indonesia. These factors are Third Party Funds (DPK), Non-Performing Financing (NPF), and Total Assets (TA). The data used in this study is panel data with the period 2010-2020 published by the Financial Ministry and in the annual financial statements of Islamic banking. The population of 21 companies with a sample of 5 companies with purposive sampling methods. The analysis tools used are Eviews10 and SPSS 18. The analysis technique in this study is a regression of panel data by testing using a fixed-effect model. The results of this study showed that DPK, NPF, and simultaneously had a significant effect on total revenue-sharing financing in sharia business units in Indonesia. The results of the study partially showed that the variables of DPK and TA had a significant positive effect on the total financing in the Sharia Business Unit in Indonesia. The NPF variable does not have a significant negative effect on the total financing in the Sharia Business Unit in Indonesia. The results of the R-Square adjusted value showed a value of 51.9%.